2003
DOI: 10.1002/ajmg.a.20526
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of limb anomalies in CHARGE syndrome: Correlation with diagnosis and characteristic CHARGE anomalies

Abstract: CHARGE syndrome was initially not thought to involve the limb. Several subsequent reports have shown that limb anomalies are not uncommon. To date, there have been no quantitative studies of limb anomalies in CHARGE syndrome. This study was designed to answer several questions: Do CHARGE patients with limb anomalies represent a subgroup within CHARGE syndrome? Are there correlations between certain CHARGE syndrome anomalies and limb anomalies? Are there differences between the two genders and associated limb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
0
16
2
Order By: Relevance
“…Nevertheless, the presence of choanal atresia together with ear defects and developmental delay points to an overlap between CHARGE and Okihiro syndromes. Since limb malformations do occur in CHARGE syndrome (Brock et al, 2003), contiguous gene deletions including SALL4 should be considered in cases diagnosed with CHARGE syndrome but without CHD7 mutation. Physical features not reported with SALL4 defects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the presence of choanal atresia together with ear defects and developmental delay points to an overlap between CHARGE and Okihiro syndromes. Since limb malformations do occur in CHARGE syndrome (Brock et al, 2003), contiguous gene deletions including SALL4 should be considered in cases diagnosed with CHARGE syndrome but without CHD7 mutation. Physical features not reported with SALL4 defects.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, limb involvement did not receive much attention in CHARGE until Brock et al [2003] studied in depth that aspect of the disorder and showed that limb involvement occurs in over onethird of CHARGE patients. This frequency is higher than that observed for other more familiar features such as esophageal atresia, part of the new diagnostic criteria proposed by Verloes [2005], so we propose that the ''E'' should expand to reflect involvement of extremities.…”
mentioning
confidence: 98%
“…Recently, limb anomalies have been reported as a rare manifestation in CHARGE syndrome [3,17,19]. On the other hand, Brock et al [4] reported that limb anomalies occurred in about 30% of patients with definite or probable CHARGE syndrome. It is interesting that limb anomalies with DiGeorge sequence are more frequently observed in male (P value <0.034), and limb anomalies were observed in 70.0% of male DiGeorge sequence with definite CHARGE syndrome [4].…”
Section: Discussionmentioning
confidence: 96%
“…Limb anomalies were not initially described in CHARGE syndrome [4]. Recently, limb anomalies have been reported as a rare manifestation in CHARGE syndrome [3,17,19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation